Distribution of boron in the rocks of central Nepal Himalaya (Journal of Nepal Geological Society, 2003)
Boron content in the rocks of central Nepal Himalaya depends upon the lithology and the grade of metamorphism. The concentration of boron is abundant (up to 322 ppm) in the metasedimentary rocks of the Lesser Himalaya. There seems to be a rather good correlation between the boron content in the rocks and the grade of metamorphism. The boron content progressively increases from chlorite to garnet isograds, then it systematically decreases in the staurolite±kyanite, kyanite and sillimanite isograds, respectively. This trend may be related to the inverse metamorphism associated with movement along the Main Central Thrust.The Manaslu leucogranite contains very high amount of boron (950 ppm). The enrichment of boron in this rock may be due to the release of boron from the Lesser Himalayan rocks during the partial melting of the Higher Himalayan Crystallines (Tibetan Slab) as a result of the movement along the MCT. Tourmaline from the Manaslu Granite is also highly rich in boron (8460 ppm).